Odpowiedzi

2010-02-06T11:49:21+01:00
∫x ln(1+x)dx,
zakładamy, ze 1 + x > 0
Metoda - całkowanie przez części
∫udv = uv - ∫vdu
u = ln(1+x), to du = dx/(x+1)
dv = x dx, to v = ∫x dx = (1/2) x²

∫ x ln(1 =x) dx = ln(1+x)*(1/2)x² - ∫(1/2)x²dx/(1 +x) =
Zajmę się teraz ∫(1/2) x² dx/(1+x) = (1/2)*∫[x²/(1+x)]dx
Ponieważ x²/(1+x) = [(x² - 1) +1 ]/(1+x) = [(x-1)(x+1) +1]/(1+x) =
= (x-1) + 1/(1+x) zatem
∫[x²/(1+x)] dx = ∫(x-1)dx + ∫ [1/(1+x) dx = ∫xdx -∫1dx+∫[1/(1+x)dx =
=( 1/2)x² -x + ln (1+x) + C1
Mamy zatem
(1/2)∫[x²/(1+x)]dx = (1/4)x² -(1/2)x+ (1/2) ln(1+x) +(1/2)C1
Ostatecznie:
∫x ln(1+x) dx = (1/2)x² ln (1+x) -(1/4)x² +(1/2)x -(1/2)ln(1+x)+C

Korzystałem z wzoru
∫[f¹(x)/f(x)]dx = ln I f(x) I + C przy obliczaniu ∫[1/(1+x)]dx
To na razie tyle.


3 3 3